KESEHATAN JIWA MASYARAKAT DALAM ANTISIPASI DI MASA PANDEMI COVID -19 DIKELURAHAN RAWANG - astri doris (Akper Kesdam I/Bukit Barisan Padang, 2021)
Coronavirus Disease (COVID-19) is the name given by WHO (World Health Organization) on February 11,2020. COVID-19 is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Thecorona virus-19 (COVID-19) not only threatens physical health, but also threatens the mental health of manypeople. Some mental disorders that have arisen today since the COVID-19 pandemic, for example, are easilycarried away by emotions, stress, excess, depression, and so on. The purpose of this study was to determinethe mental health of the community during the COVID-19 pandemic. This type of research is descriptivequantitative research. Sampling technique using simple random sampling as many as 150 people. The resultsshowed that of 150 people, 125 people or (83.3%) had mental health during the pandemic period, 23 (15.3%)were at risk for mental health during the pandemic and 2 (1.3%) experienced disturbances during thepandemic. covid-19 pandemic.